Oocyte Source and Hormonal Stimulation for In Vitro Fertilization Using Sexed Spermatozoa in Cattle - Giorgio A. Presicce; Jie Xu; Guochun Gong; Juan F. Moreno; Sanjeev Chaubal; Fei Xue; Antonino Bella; Elena M. Senatore; Xiangzhong Yang; X. Cindy Tian; Fuliang Du (Veterinary Medicine International)
The aim of this study was to investigate the efficiency of in vitro embryo production in cattle utilizing sexed sperm from two bulls and oocytes recovered by OPU. Twenty donor animals were employed in eight OPU replicates: the first four OPU trials were conducted on animals without hormone treatment, and the last four were run on the same animals, following FSH subcutaneous and intramuscular administration. A higher rate of blastocyst development was recorded in stimulated, as compared to nonstimulated animals, (25.2% versus 12.8%, 𝑃=.001). Ocytes derived from slaughterhouse (SH) ovaries were also fertilized with sperm from the same bulls. Overall, non-sexed sperm used with oocytes derived from SH ovaries was significantly more efficient for blastocyst development than was sexed sperm with these same SH derived oocytes and sexed sperm with stimulated donor oocytes (39.8% versus 25.0% and 25.2%, 𝑃=.001). In conclusion, the use of sexed sperm with OPU-derived oocytes resulted in a significantly higher blastocyst development when donors were hormonally stimulated; furthermore, the level of efficiency achieved was comparable to that attained when the same sexed sperm was tested on oocytes derived from SH ovaries.